Recent Trends in Azeotropic Mixture Separation: A Comprehensive Review - Christel Cortel; Kristine Oira Flordeliza; Shayne Ruzzel A. Galvez; Maria Angeline Magalong; Trisha Mae G. Mendoza; Rubi Vicente C. Rubi (Engineering Proceedings, 2024)
In the chemical and process industries, different techniques are implemented to enable the separation of azeotropic mixtures. These separation methods are broadly classified as azeotropic distillation procedures, which employ the use of entrainers, and membrane-based processes, which mainly use semi-permeable membrane materials. This paper seeks to examine the current trends employed in the separation procedures for azeotropic mixtures in industry, particularly the techniques and methods applied in the actual processes. Additionally, this paper also outlines the common issues encountered in the current setups for the separation of azeotropic mixtures. Several studies show that in comparison to conventional separation techniques, the application of alternative distillation methods and advanced membrane-based techniques for the separation of azeotropic mixtures results in better separation efficiency and reduced energy consumption while also maintaining the cost-effectiveness of the overall process. In addition to this, advancements in the available techniques for separation would also improve the viability and ensure the long-term sustainability of the proposed developments, addressing the current gaps in knowledge while ensuring that existing challenges in the procedures, like membrane fouling and limited scalability, are properly addressed. Furthermore, this paper also highlights the research outlook of the processes involved in the separation of azeotropic mixtures.